The effect of short-term endurance and strength training on motor unit conduction velocity - Vila-Chã, Carolina (2011)
AIM: The aim of this study was to investigate the effect of strength and endurance training on the conduction velocity of vastus medialis obliquus and lateralis single motor units during voluntary sustained knee extensions. METHODS: Seventeen sedentary healthy men (age, mean ± SD, 26.3 ± 3.9 yr) were randomly assigned to one of 2 groups: strength training (ST, n= 8) or endurance training (ET, n= 9). Conventional endurance and strength training was performed three days per week, over a period of 6 weeks. Motor unit conduction velocity (MUCV), maximum voluntary force (MVC) and time-to-task failure at 30% MVC of the knee extensors were measured before and immediately following training. To assess MUCV, multi-channel surface and intramuscular EMG signals were concurrently recorded from the vastus medialis obliquus (VMO) and vastus lateralis (VL) muscles during 60-s isometric knee extensions at 10% and 30% of MVC. RESULTS: After 6 weeks of training, MVC increased in the ST group (16.7 ± 7.4 %; P < 0.05) whereas time to task failure was prolonged in the ET group (33.3 ± 14.2 %; P < 0.05). Both training programs induced an increase in motor unit conduction velocity at both 10% and 30% MVC (P < 0.01). Furthermore after both training programs, the reduction in MUCV over time during the sustained contractions occurred at slower rates compared to baseline (P < 0.01). CONCLUSION: These results indicate that short-term endurance and strength training induce similar alterations of the electrophysiological membrane properties of the muscle fiber and in their changes during sustained contractions